Analisis Yuridis Bentuk Surat Dakwaan Jaksa Penuntut Umum Dalam Perkara Tindak Pidana Korupsi (Studi Kasus Korupsi Pada Kejaksaan Negeri Kabanjahe) - Azwarman Azwarman; Syafruddin Kalo; Madiasa Ablisar; Jelly Leviza (Iuris Studia: Jurnal Kajian Hukum, 2021)
The selection of the indictment is very important for the Public Prosecutor. The process of the selection of an indictment by the public prosecutor started an investigation docket study, then the results of research Prosecutors can identify what evidence and the strength of proof is met, then to the inherent weaknesses in the know on the docket to prepare juridical facts accurate to anticipate problems that arise in efforts to prove in court. The selection of the indictment also affect the process of evidence in court because it forms the indictment prosecutors effect to the provisions of an offense must be proved before the court. The problem this thesis is how Prosecutors preparing indictments corruption cases especially using paragraph of article 2 (1) and Article 3 of Law No.. 31 of 1999 and Act No.. 20 of 2001 in the State Attorney Kabanjahe. How the juridical consequences of the indictment Prosecutors at the State Attorney Kabanjahe stacking subsideritas in the examination at the trial.The writing of this thesis used the type of normative juridical methods with the consideration that the issues studied were relevant to regulations and how they handled in judicial practice. From the nature of the study is a descriptive analysis, which is planning a systematic, factual and accurate statement of facts. on the theory of proof systems that are used by the Criminal Procedure Code verification system negatief statutory (negatief wettelijk overtuiging). The thesis used this research method to approach the problem by using the approach of legislation (approach approach) and case approach (case approach).From the results of the research done, it could be summed up as follows: first, Preparation Prosecution indictment on the State Attorney Kabanjahe in corruption cases that use Article 2 paragraph (1) and Article 3 of Law No.. 31 of 1999 and Act No.. 20 of 2001 is in the form of an indictment that vary, sometimes in the form of alternative charges and also in the form of the indictment subsideritas. Second, For the Public Prosecutor to handle corruption cases where criminal charges stated defendant was found guilty of the offenses charged in the indictment primary, but then the judge decided the defendant guilty of the charges of expressed attitudes subsidiary prosecutor to assert legal remedies against the decision